2016
DOI: 10.1007/s12072-015-9699-9
|View full text |Cite
|
Sign up to set email alerts
|

Ritonavir-boosted danoprevir-based regimens in treatment-naive and prior null responders with HCV genotype 1 or 4 and compensated cirrhosis

Abstract: Treatment with danoprevir/r-based regimens for 24 weeks is safe and well tolerated in CHC patients with compensated cirrhosis. A quadruple therapy regimen (danoprevir/r, mericitabine, peginterferon alfa/ribavirin) produced high SVR24 rates in prior null responders, particularly among G1b patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… 32 Another phase 2b study (RUSHMORE) reported SVR24 (61.1%, 11/18) of the above regimen in cirrhotic HCV GT-1-infected patients who previously exhibited null responses. 25 (iii) Danoprevir/r plus mericitabine and ribavirin for 24 weeks offered SVR24 <65% in non-cirrhotic HCV-infected patients based on two phase 2 studies: INFORM-SVR 31 and MATTERHORN ( Table 1 ). 32 The above findings revealed the potential of danoprevir/r in interferon-free regimens, but future studies are yet to evaluate the interferon-free ribavirin-free regimens of danoprevir plus other DAAs such as sofosbuvir.…”
Section: Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“… 32 Another phase 2b study (RUSHMORE) reported SVR24 (61.1%, 11/18) of the above regimen in cirrhotic HCV GT-1-infected patients who previously exhibited null responses. 25 (iii) Danoprevir/r plus mericitabine and ribavirin for 24 weeks offered SVR24 <65% in non-cirrhotic HCV-infected patients based on two phase 2 studies: INFORM-SVR 31 and MATTERHORN ( Table 1 ). 32 The above findings revealed the potential of danoprevir/r in interferon-free regimens, but future studies are yet to evaluate the interferon-free ribavirin-free regimens of danoprevir plus other DAAs such as sofosbuvir.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…The clinical efficacy of danoprevir has been evaluated by nine clinical studies (Table 1). In addition to the RUSHMORE study (phase 2a, NCT01483742) which recruited cirrhotic patients, 25 the other eight studies reported the clinical efficacy of danoprevir in noncirrhotic patients, including the MANASA study (phase 3, NCT03020082), 26 a phase 2/3 study (NCT03362814), 27 the DAUPHINE study (phase 2b, NCT01220947), 28 the MAKALU study (phase 2, NCT03020004), 29 the EVEREST study (phase 2, NCT03020095), 30 the INFORM-SVR study (phase 2, NCT01278134), 31 a phase 2 study (NCT01331850), 32 and a phase 1 study (NCT01185860). 33 Among these studies, the approved danoprevir-based regimen (danoprevir 100 mg twice daily (BID) plus ritonavir 100 mg twice daily; peginterferon alpha-2a 180 μg once weekly; and ribavirin 1000 mg/day for bodyweight <75 kg, 1200 mg/day for ≥75 kg, twice daily for 12 weeks) in treatment-naïve noncirrhotic patients was evaluated by the MANASA study, 26 the MAKALU study, 29 the DAUPHINE study, 28 and a phase 1 study (NCT01185860).…”
Section: Clinical Efficacymentioning
confidence: 99%
“…NS3/4A is a prime drug target for HCV DAAs combination therapies. There have been at least 6 PIs, including telaprevir, boceprevir, simeprevir, asunaprevir, paritaprevir, and grazoprevir, approved for clinical use to treat HCV-infected patients [3], and more are still under investigation [26]. The potency of PIs has been verified in tens of trials, either in combination with IFNs or with other DAAs [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infection with hepatitis C virus (HCV) has been reported to affect 170 million people worldwide. Approximately 700,000 people die each year from HCV-related complications [1][2][3]. HCV is a leading cause of liver fibrosis and cirrhosis that may eventually lead to hepatocellular carcinoma [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation